Morphology, Life Cycle, Environmental Factors and Fitness – a Machine Learning Analysis in Kissing Bugs (Hemiptera, Reduviidae, Triatominae) - Rabinovich, Jorge E. (Frontiers in Ecology and Evolution, 2021)
Populations are permanently evolving and their evolution will influence their survival and reproduction, which will then alter demographic parameters. Several phenotypic, life history and environmental variables are known to be related to fitness measures. The goal of this paper was to look into the possible types of those relationships in insects of the subfamily Triatominae, vectors of Trypanosoma cruzi, the causative agent of Chagas disease. After an exhaustive literature review of 7207 records of publications referring exclusively to all possible features of the triatomines, using 15 keywords those records were reduced to 2968 publications, that were analyzed individually; after deleting those publications that didn’t have the data in quantitative form as needed for the objective of this paper, I found that 171 papers were adequate for the present analysis. From them I compiled a dataset of 11 variables and 90 cases from 36 triatomine species. Those variables included four environmental, two life cycle, and four morphological variables, and one demographic parameter: a fitness measure (the population intrinsic rate of natural increase, r0), used as dependent variable. I resorted to the Random Forest method as a machine learning approach for the analysis of this dataset, and found that -in addition to the triatomine species themselves- only the two life cycle variables (mean development time from egg to adult, and mean fecundity, expressed as the average number of female eggs laid per female per day) were statistically significant in determining fitness (r0). The machine learning approach used in the analysis provided a similar but deeper insight into these relationships than classical regression. Except for an analysis on senescence, this is the first study in triatomines addressing these questions. These results will be useful for other theoretical optimization approaches (frequency-dependence, density-dependence, evolutionary game theory, and adaptive dynamics), thus contributing to the theoretical framework for interpreting the succession of stages in insect adaptations, a framework yet to be constructed.